GALERI SENI KALIGRAFI ISLAM DI MARTAPURA - Hasnawati, Noor; Huzairin, Muhammad Deddy (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Islamic Calligraphy Art Gallery is a place that accommodates calligraphy artworks to make it easier for people to know, learn, and obtain one of the Islamic Cultural Arts namely Calligraphy. This goal can be achieved by realizing a design that can attract attention and can introduce Islamic calligraphy to the community and is strategically located. Thus, the Islamic Calligraphy Art Gallery that will be designed is a gallery in Martapura that is expressive and educational towards Islamic calligraphy art by applying calligraphy elements into the form, space, and architectural order. The problem is answered using concrete and abstract metaphorical methods. Islamic calligraphy is a single series of letters composed of beautiful compositions. In addition, Islamic Calligraphy also contains a philosophy about the meaning it contains. Islamic calligraphy forms and philosophies are analyzed into spaces, shapes, and architectural settings to create educational and expressive gallery designs. Elements of Islamic calligraphy are depicted in the form of building masses, textures, colors, and facades (concrete metaphors). While the philosophy or meaning of calligraphy is described on mass orientation, achievement, circulation, space, and sequence flow (abstract metaphor).